Prevalence and Pattern of Premenstrual Syndrome among Secondary School Students in Kaduna State - Suleiman, Aisha; Yahya, Anisah; Oguntayo, Adekunle (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context: Menstruation may be associated with somatic and psychological symptoms of premenstrual syndrome.Aims: We determined the awareness, prevalence, and pattern of premenstrual syndrome among female students in secondary schools in Kaduna state. Association of premenstrual syndrome with sociodemographic profile of respondents and healthcare evaluation and intervention sought by students with premenstrual syndromes were also explored.Materials and Methods: It was a cross-sectional observational study conducted on 300 students enrolled in secondary schools in Sabon Gari Local Government Area in Kaduna state. A pretested questionnaire was used to obtain data. The data were analysed using SPSS 20 withP< .05 considered as significant.Results: The mean age of participants was 16.2 ± 1.6 years. The prevalence of premenstrual syndrome was 226 (75.3%). Dysmenorrhea was the most common physical manifestation of premenstrual syndrome and occurred in 183 (81.0%) of the respondents with premenstrual syndrome with a median pain score of 3.0, while mood swings were the most common emotional manifestation of premenstrual syndrome present among respondents 132 (58.4%). Healthcare evaluation was sought by only 15.4% of those affected; however, a good number (42.5%) sought for some form of intervention for their symptoms. There was no significant association between the occurrence of premenstrual syndrome and the sociodemographic profile of the respondents.Conclusion: The self-reported prevalence rate of premenstrual syndrome among the study population is high with dysmenorrhea being the most common symptom. There was no association found between the occurrence of premenstrual syndrome and sociodemographic profile of those affected. Most of the students affected did not seek for any form of healthcare evaluation.
Keywords: Kaduna; pattern; premenstrual syndrome; prevalence; secondary school girls